Estimación de la NAIRU para México, 2002Q1-2018Q2 - Eduardo Loría Díaz; Javier Valdez; Raúl Tirado (Investigación Económica, 2019)
– We estimate the Non-Accelerating Inflation Rate of Unemployment (NAIRU) for Mexico (2002Q1-2018Q2) with Ball and Mankiw's (2002) methodology using the Generalized Method of Moments. We prove that, with this methodology, the calculation of NAIRU is more efficient than the one calculated with the HP filter. We show that: a) the Dot Com and the Great Recession crises have had real and lasting effects on the labor market; b) Mexico's monetary policy has been stabilizing, and c) the relationship between unemployment and inflation has strengthened over the last years.
Keywords: C26; E12; E24; E52; E58; 330; NAIRU; brecha de desempleo; política monetaria; GMM; cambio estructural